Molecular Mechanisms and Clinical Effects of Medicinal Plants in Modulating Oxidative Stress: A Systematic Review from Athletic Performance to Vital Organ Protection - Isma Nur Azzizah; Endah Wati Zahroh; Arifiana Wungu Kartika Dewi; Dini Aulia Cahya (Fakultas Kedokteran Universitas Jenderal Soedirman, 2026)
Oxidative stress constitutes a major pathophysiological mechanism in conditions ranging from exercise-induced muscle fatigue to chronic organ damage including diabetic nephropathy and ischemic stroke. Medicinal plants offer therapeutic potential through bioactive compounds that modulate cellular defense pathways. This systematic review evaluated the molecular mechanisms and clinical efficacy of medicinal plants (Kaempferia galanga, Nigella sativa, Panax ginseng, and other herbal formulations) in managing oxidative stress across diverse health contexts. A comprehensive literature search was conducted using reputable databases. Studies measuring oxidative stress biomarkers (MDA, SOD) and cellular signaling pathways (Nrf2, NF-κB, PI3K/AKT) were included. Results showed that N. sativa and K. galanga supplementation in athletes significantly reduced MDA levels and inflammatory cytokines (IL-6), accelerating post-exercise recovery. Bioactive compounds including Ginsenoside Ro and Kaempferide demonstrated organ-protective effects through Nrf2/HO-1 activation, autophagy promotion, and mitochondrial protection in ocular and renal tissues. These findings indicate that medicinal plants exert cytoprotective effects by activating endogenous antioxidant systems. The therapeutic spectrum spanning athletic performance enhancement to chronic organ protection underscores the translational potential of herbal interventions as promising antioxidant agents.